Strain-rate sensitivity of the lateral collateral ligament of the knee - Bonner,TJ; Newell,N; Karunaratne,A; Pullen,AD; Amis,AA; Bull,AMJ; Masouros,SD (Journal of The Mechanical Behavior of Biomedical Materials, 2015)
The material properties of ligaments are not well characterized at rates of deformation that occur during high-speed injuries. The aim of this study was to measure the material properties of lateral collateral ligament of the porcine stifle joint in a uniaxial tension model through strain rates in the range from 0.01 to 100/s. Failure strain, tensile modulus and failure stress were calculated. Across the range of strain rates, tensile modulus increased from 288 to 905 MPa and failure stress increased from 39.9 to 77.3 MPa. The strain-rate sensitivity of the material properties decreased as deformation rates increased, and reached a limit at approximately 1/s, beyond which there was no further significant change. In addition, time resolved microfocus small angle X-ray scattering was used to measure the effective fibril modulus (stress/fibril strain) and fibril to tissue strain ratio. The nanoscale data suggest that the contribution of the collagen fibrils towards the observed tissue-level deformation of ligaments diminishes as the loading rate increases. These findings help to predict the patterns of limb injuries that occur at different speeds and improve computational models used to assess and develop mitigation technology.